2015
DOI: 10.2514/1.b35331
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Performance of Shroudless Turbine Blade Tips with Relative Casing Movement Effects

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 50 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…The y + of the first grid point away from the tip was between 1 and 3, with a mean value of 2 whilst the remainder of the blade had an average y + of 3. This was considered sufficient to ensure resolution of the viscous sub-layer and is consistent with recent aerodynamic work of Schabowski et al (2014) [37] (tip y + ≈ 4) and aerothermal work of Virdi et al (2015) [38] (tip y + largely between 1 and 3) who demonstrated close agreement between CFD and experiment. Figure 7 shows the experimentally measured tip surface heat flux along the camber line.…”
Section: Computational Set-upsupporting
confidence: 86%
“…The y + of the first grid point away from the tip was between 1 and 3, with a mean value of 2 whilst the remainder of the blade had an average y + of 3. This was considered sufficient to ensure resolution of the viscous sub-layer and is consistent with recent aerodynamic work of Schabowski et al (2014) [37] (tip y + ≈ 4) and aerothermal work of Virdi et al (2015) [38] (tip y + largely between 1 and 3) who demonstrated close agreement between CFD and experiment. Figure 7 shows the experimentally measured tip surface heat flux along the camber line.…”
Section: Computational Set-upsupporting
confidence: 86%
“…Another factor pertinent to the present interest is the relative movement of casing. This can clearly affect the extent of transonic portion of the tip flow as shown computationally by Zhang et al (2011b); Coull and Atkins (2015); Virdi et al (2015). Some recent data for a rotating facility have been gathered by Acharya (2016a, 2016b).…”
Section: Discussionmentioning
confidence: 95%
“…The dependence of heat transfer patterns on OTL flow regime can be further examined by studying the sensitivity of the flow to tip gap size. Circumferentially averaged heat transfer coefficients (HTCs) along axial chord for a transonic flat tip are shown in Figure 7 (Virdi et al, 2015). The subsonic flow part (x/Cx<0.5) shows a classic trend of decreasing heat transfer with smaller tip gaps.…”
Section: Overall Heat Transfer Characteristics In High Speed Flowmentioning
confidence: 99%
“…Dunn and Haldeman 14 and Virdi et al. 15 also investigated the heat transfer performance of the blade tip with experimental measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and He 13 found that the tip choking caps the tip leakage mass flow rate in the transonic condition. Dunn and Haldeman 14 and Virdi et al 15 also investigated the heat transfer performance of the blade tip with experimental measurement.…”
Section: Introductionmentioning
confidence: 99%